(untitled) (Res Medica, 2013)
I must confess at the outset that the subject of hysteria still awaits an adequate definition but the following one is as good as any so far produced. "Hysteria is a person’s response to environmental difficulties, which makes it impossible for that person to perform his duties." Hysteria can be considered as subconscious malingering, but this concept too, fails to be comprehensive. In making the diagnosis of hysteria the following aspects should be considered: The personality of the patient. Dissociation. Suggestion. The actual clinical features. The role of organic and psychological factors. Perhaps the most salient feature of hysteria is its propensity to occur more commonly in people with what is known as a hysterical personality.